Imaging findings of primary hepatic leiomyosarcoma: a case report and literature review - Yan, Lifen; Huang, Runqian; Chen, Shuting; Chen, Jiawei; Li, Jinglei (Frontiers in Oncology, 2024)
Primary hepatic leiomyosarcoma (PHLS) is an extremely rare malignant tumor, which is often elusive in early diagnosis due to its rarity and nonspecific clinical and imaging presentations. Herein, we present a case of PHLS in a 66-year-old male and a review of the English literature from January 2000 to December 2023, focusing on the clinical and imaging characteristics of 30 patients with PHLS. The present patient was admitted to our hospital with complaints of abdominal distension, with history of hepatitis B. Tumor markers, including alpha-fetoprotein, carcinoembryonic antigen, and CA 19-9, were within the normal range. A hepatic tumor was incidentally identified during an abdominal ultrasound examination, further evaluated by contrast-enhanced CT and MR scans, which was preliminarily misdiagnosed as hepatocellular carcinoma. The tumor was surgically excised and definitively diagnosed as PHLS, characterized by two distinct areas with varying imaging features on contrast-enhanced CT and MR images. PHLS typically manifests as a well-defined, heterogeneously hypo- or iso-dense mass on CT, with a slightly prolonged T2 signal on MRI, and exhibits gradual enhancement during dynamic contrast-enhanced imaging. We advocate that the possibility of PHLS should be considered when the aforementioned imaging features are observed.